If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+1)(x+2)(x+3)(x+4)+24=0
We multiply parentheses ..
(+x^2+2x+x+2)(x+3)(x+4)+24=0
We multiply parentheses ..
(+x^2+2x+x+2)(+x^2+4x+3x+12)+24=0
We move all terms containing x to the left, all other terms to the right
(+x^2+2x+x+2)(+x^2+4x+3x+12)=-24
| d-6=6-4 | | (3x-15)+(2x+35)=180 | | 7+5k=8+1k | | r/5=12 | | 5-6x=8+11x | | 2-3x+1/4=2(2x+1)/3-5x-1/2 | | x+24-8=7 | | 9×+y=5 | | 10(-5b+9)=91-50b | | x-14+6=5 | | x/4=3,x/5=4 | | -v/7=-27 | | 4m+7=42 | | r+47=1 | | (x+12)(x-3)-x(x+5)=24 | | 0.5(-4+6x)=0.33+0.66(x+9) | | 8.3+x=9 | | -7x=4-8=24 | | 16.6(x-9)=25 | | 5x-18=3x-+42 | | -31=w/3 | | 17x-2=2x+16=x=5 | | -31=w/3= | | 7-(4-x)=9-2x | | 5f=−8 | | 2m^2-2m-24=0 | | -2+x-9=-3 | | 1−2(-4+6x)=1−3x+2−3(x+9) | | -f-3=14 | | 2x-18+4x+38=180 | | 1/2n=71/2 | | 7=4b |